The Effect of Customer Bonding, Customer Experience, and Service Quality Satisfaction on Customer Loyalty At Novi Tenggarong Salon - Ondi Prawiradinata; Fitroh Adhilla; Zunan Setiawan (International Journal of Sociology of Religion, 2026)
Increasingly fierce competition in the beauty services industry has prompted small businesses such as Salon Novi in Tenggarong to prioritize customer loyalty as a key determinant of business sustainability. A quantitative survey approach was used, involving 75 customer respondents selected through probability sampling from a monthly population of 150 customers. Data were collected using a Likert-scale questionnaire and analyzed via multiple linear regression, supplemented by an F-test for simultaneous effects and a t-test for partial effects. The results indicate that customer bonding, customer experience, and service quality simultaneously exert a significant influence on customer loyalty. Partially, all three variables were significant, with service quality emerging as the most dominant (r = 0.486), followed by customer experience (r = 0.472) and customer attachment (r = 0.287), indicating that service quality is the most decisive variable for customer loyalty at Salon Novi Tenggarong.